HYBRID SYSTEMS FOR WASTEWATER TREATMENT - Vicuña G., E. (2009)
The treatment of wastewater is facing, in the curren! context, a greater number of challenges and demands such as: higher environmental standards, treatment of more complex substances and in high amounts, reuse and recycling demand, little space available to install or retrofit treatment plants. Within this context, treatment systems called hybrids appear; which combine, in a synergetic way, the work of individual processes, enhancing positive aspects and inhibiting or eliminating adverse ones. The hybrid treatment systems are very efficient, compact, and cost-effective, due that they can treat any kind of pollutant and higher volumes than conventional ones. lt is of interest , in this project, to treat wastewater from textile índustry and water bodies affected by oil spills, consequently hybrid treatments which contain biological components are the bes! alternative in treat these wastewaters, due to: a) high versatility in treat different pollutant types; b) easy management, capacity to be retrofitted , and low complexity in operating them; e) are efficient, capable to eliminate almos! 100% of organic compounds and may others; d) cost-effective process as they do not require mechanical parts neither high labor, which could increase expenditure in operation and energy used.